Abnormal birth weights for gestational age in relation to maternal characteristics in Sweden: a five year cross-sectional study - Min Wai Lwin; Erika Timby; Anneli Ivarsson; Eva Eurenius; Masoud Vaezghasemi; Sven-Arne Silfverdal; Marie Lindkvist (BMC, 2023)
Abstract Background Abnormal birth weight - small for gestational age (SGA) and large for gestational age (LGA) - are important indicators for newborn health. Due to changes in lifestyle in recent decades, it is essential to keep up-to-date with the latest information on maternal factors linked to abnormal birth weight. The aim of this study is to investigate SGA and LGA in relation to maternal individual, lifestyle and socioeconomic characteristics. . Methods This is a register-based cross-sectional study. Self-reported data from Sweden's Salut Programme maternal questionnaires (2010-2014) were linked with records in the Swedish Medical Birth Register (MBR). The analytical sample comprised 5089 singleton live births. A Swedish standard method using ultrasound-based sex-specific reference curves defines the abnormality of birth weight in MBR. Univariable and multivariable logistic regressions were used to examine crude and adjusted associations between abnormal birth weights and maternal individual, lifestyle and socioeconomic characteristics. A sensitivity analysis, using alternative definitions of SGA and LGA under the percentile method, was undertaken. Results In multivariable logistic regression, maternal age and parity were associated with LGA (aOR = 1.05, CI = 1.00, 1.09) and (aOR = 1.31, CI = 1.09, 1.58). Maternal overweight and obesity were strongly associated with LGA (aOR = 2.28, CI = 1.47, 3.54) and (aOR = 4.55, CI = 2.85, 7.26), respectively. As parity increased, the odds of delivering SGA babies decreased (aOR = 0.59, CI = 0.42, 0.81) and preterm deliveries were associated with SGA (aOR = 9.46, CI = 5.67, 15.79). The well-known maternal determinants of abnormal birthweight, such as unhealthy lifestyles and poor socioeconomic factors, were not statistically significant in this Swedish setting. Conclusions The main findings suggest that multiparity, maternal pre-pregnancy overweight and obesity are strong determinants for LGA babies. Public health interventions should address modifiable risk factors, especially maternal overweight and obesity. These findings suggest that overweight and obesity is an emerging public health threat for newborn health. This might also result in the intergenerational transfer of overweight and obesity. These are important messages for public health policy and decision making.